PELATIHAN MICROSOFT WORD PADA SISWA SISWI SMP NEGERI 1 KEDUNGBANTENG - Rivellia Yulianti Tajudin; Azzahira Dianinka Nur Rahma; Zamita Muyassaroh; Amanda Bunga Aulia; Ito Setiawan (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The fast advancement of information technology demands that students develop digital literacy skills, including proficiency in using word processing software such as Microsoft Word. However, in practice, many students have not yet fully mastered its use, especially in terms of proper document formatting. This study is intended to assess the effectiveness of Microsoft Word training in enhancing students’ competencies at SMP Negeri 1 Kedungbanteng. A descriptive qualitative approach was employed, with data collected through observation and questionnaires. The training was implemented using a hands-on method, enabling students to engage actively and gain practical experience. The findings indicate that the training produced a highly positive outcome, with all participants (100%) reporting an understanding of the material. Furthermore, 59.1% of students agreed and 40.9% strongly agreed that the material was easy to follow and useful. There was also a noticeable improvement in students’ technical skills in document preparation, including margin settings, text formatting, and table insertion. Additionally, the training boosted students’ confidence and motivation to learn technology. In conclusion, hands-on Microsoft Word training is proven to be effective in enhancing students’ fundamental skills and digital literacy. The results also emphasize the importance of implementing continuous practice-based training to support learning in the digital age.